Visual Rhetoric in Political Cartoons: A Structuralist Approach - Morris, Ray (Metaphor and symbolic activity, 1993)
Visual rhetoric has become of interest to sociology as part of the study of how groups are defined and presented. A structuralist approach to metaphor may help attempts to describe the ways that political cartoons portray groups, using individuals to stand for groups, and familiar, simple contrasts to stand for complex, competing powers. Rhetorical devices used in cartoons include condensation, combination, domestication, opposition, carnivalization, and hypercarnivalization.